2005
DOI: 10.1590/s1519-566x2005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Tegumentary epithelial glands in the abdomen of virgin and physogastric queens of the stingless bee Scaptotrigona postica Latreille (Meliponini: Trigonina)

Abstract: Neotropical Entomology 34(1):041-045 (2005) Glândulas Tegumentares Epiteliais no Abdome de Rainhas Virgens e Fisogástricas de Scaptogrigona posticaLatreille (Meliponini: Trigonina)RESUMO -Nas operárias das abelhas eussociais, regiões do epitélio tegumentar do abdome podem hipertrofiar-se e tornarem-se glandulares, sendo responsáveis pela produção de cera usada na contrução dos alvéolos de cria. Nos meliponíneos, epitélio com essas características também foi observado nas rainhas, porém sua função ainda continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…In S. quadripunctata, some virgin queens were seen manipulating the wax in the area of the involucrum, beginning the construction of prison chambers. Abdalla et al (2005) found well-developed wax glands in both workers and queens. The queens produce the wax used for the construction of the cerumen prison chambers.…”
Section: Discussionmentioning
confidence: 86%
“…In S. quadripunctata, some virgin queens were seen manipulating the wax in the area of the involucrum, beginning the construction of prison chambers. Abdalla et al (2005) found well-developed wax glands in both workers and queens. The queens produce the wax used for the construction of the cerumen prison chambers.…”
Section: Discussionmentioning
confidence: 86%